Treatment of Meat Industry Wastewater Using Electrochemical Treatment Method - Pinedo-Hernandez,Jose (2015)
In this work, electrocoagulation (EC) was used to treat meat industry (frigorific) wastewater. Effects of EC process variables such as distance between electrodes and potential on the removal efficiency of chemical oxygen demand (COD), were examined. Two factors with three levels response surface design coupled with response surface methodology (RSM) were employed to optimize the EC process variables. Second order polynomial models were developed for the responses and three dimensional (3D) response surface plots were used to study the interactive effects of the process variables on the EC efficiency. Experimental results showed that EC treatment, using a potential of 40 V and electrodes with a 3 cm gap between them, presented a COD removal of over 90% for the meat industry wastewater.